Investigating the Acid Failure of Aluminium Alloy in 2 M Hydrochloric Acid Using Vernonia amygdalina - Omotosho, Olugbenga A.; Ajayi, Oluseyi O. (ITB Journal Publisher, LPPM ITB, 2012)
The acid failure of aluminium alloyÂ in 2 M hydrochloric acid solution in the presence of Vernonia amygdalina extract was investigated using gasometric technique. Aluminium alloy coupons of dimension 4 cm by 1 cm were immersed in test solutions of free acid and also those containing extract volumes of 2, 3, 4 and 5 cm3 at ambient temperature for 30 minutes. The volumes of hydrogen gas evolved as a result of the rate of reaction were recorded and analyzed. Analysis revealed that maximum inhibitor efficiency which corresponds to the lowest corrosion rate was obtained at optimum inhibitor volumes of 5 cm3, with reduction in the corrosion rate observed to follow in order of increasing extract volumes. Adsorption study revealed that Temkin isotherm best described the metal surface interaction with the extract phytochemicals, with 12 minutes becoming the best exposure time for the phytochemicalsÂ to adsorb to the metal surface at all volumes. Statistical modelling of the corrosion rate yielded an important relationship suitable for estimating corrosion rate values once volumes of the extract is known. Microstructural studies, showed an indirect relationship between crack growth rates and extract volumes, while consistency of the irregular intermetallic phases increases with increasing extract volumes.